Current Perspectives on Western Boreal Forest Life: Ethnographic and Ethnohistoric Research in Late Prehistoric and Historic Archaeology - A Preface - Arundale, Wendy H.; Clark, Donald W.; Quick, Polly McW. (ARCTIC, 1989)
At the 1987 Society for American Archaeology Meetings in Toronto, several scholars gathered to present their most recent research using ethnographic and ethnohistoric information to study late prehistoric and historic Athabaskan archaeology in the western subarctic interior. . The papers from this symposium make up the rest of this volume; this preface provides the reader with some background for better appreciating the papers that follow. The preface begins with a short historical summary of recent Athabaskan archaeology, including the use of ethnohistoric and ethnographic approaches. It continues with very brief summaries of the six papers as context for the subsequent comments, presented at the session by the symposium's two discussants, Polly McW. Quick and Donald W. Clark. Their comments touch on several important issues, including adaptation to environmental variability, the importance of explicit linkages between ethnographic information and archaeology, the value of oral history, the difficulties of projecting findings from recent historic sites back even to more distant historic sites, the promise and problems of interpreting social groupings from structural remains, the value of having northern researchers who live and work throughout the year in the North, and the need for better frameworks for linking ethnographic and ethnohistoric information with archaeology to permit some generalization. The preface closes with a discussion of future research directions and priorities. .Key words: Alaska, archaeology, Athabaskans, boreal forest, Canada, ethnoarchaeology, ethnography, ethnology, ethnohistory, historic period, research priorities, Subarctic, symposium Mots clés: Alaska, archéologie, Athabaskans, forêt boréale, Canada, ethnoarchéologie, ethnographie, ethnologie, ethnohistoire, période historique, priorité dans la recherche, subarctique, symposium